2018
DOI: 10.1038/s41598-018-31052-x
|View full text |Cite
|
Sign up to set email alerts
|

In vivo optic nerve head mechanical response to intraocular and cerebrospinal fluid pressure: imaging protocol and quantification method

Abstract: This study presents a quantification method for the assessment of the optic nerve head (ONH) deformations of the living human eye under acute intraocular pressure (IOP) elevation and change of cerebrospinal fluid pressure (CSFP) with body position. One eye from a brain-dead organ donor with open-angle glaucoma was imaged by optical coherence tomography angiography during an acute IOP and CSFP elevation test. Volumetric 3D strain was computed by digital volume correlation. With increase in IOP the shear strain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 42 publications
(37 reference statements)
1
41
0
Order By: Relevance
“…Although the findings in both of these studies represent relatively longer term changes in the position of the retinal vessels in relation to the degree of progressive glaucomatous ONH damage, which may result from remodeling within the retina, they do suggest that forces may be exerted along the retinal vessels as a result of glaucomatous ONH deformation. Additional supporting evidence was reported recently by Fazio et al, 77 who found that upon acutely and independently altering IOP or cerebrospinal fluid pressure in eyes of living human organ donors, biomechanical strains within the peripapillary retina were greatest in magnitude along the vasculature as compared with the neighboring neural retina.…”
Section: Why Might These Retinal Oct Findings Occur More Frequently Isupporting
confidence: 80%
See 1 more Smart Citation
“…Although the findings in both of these studies represent relatively longer term changes in the position of the retinal vessels in relation to the degree of progressive glaucomatous ONH damage, which may result from remodeling within the retina, they do suggest that forces may be exerted along the retinal vessels as a result of glaucomatous ONH deformation. Additional supporting evidence was reported recently by Fazio et al, 77 who found that upon acutely and independently altering IOP or cerebrospinal fluid pressure in eyes of living human organ donors, biomechanical strains within the peripapillary retina were greatest in magnitude along the vasculature as compared with the neighboring neural retina.…”
Section: Why Might These Retinal Oct Findings Occur More Frequently Isupporting
confidence: 80%
“…In order to test the hypothesis that these retinal defects develop as a result glaucomatous ONH deformation and the differential strains it may cause throughout the peripapillary retina, it would be interesting to apply 3D strain mapping techniques to acute and longitudinal deformations captured by OCT. 77,85 With the addition of adaptive-optics and MHz acquisition speeds, OCT can achieve spatial and temporal resolution capable of revealing details and dynamic activity of individual cells within the inner retina. 86 It may someday be possible to study biomechanical strain responses at the cellular level in the living human eye.…”
Section: Unifying Theory Proposedmentioning
confidence: 99%
“…We removed the spatial autocorrelation by specifying a rational quadratic spatial correlation structure using the Cartesian distance between the elements in each model. 44 We used α = 0.01 to establish significance. Statistical analysis was done with R 3.5.1 (R Foundation for Statistical Computing, Vienna, Austria).…”
Section: Discussionmentioning
confidence: 99%
“…First, optical coherence tomography scans show that LC defects are often located at the periphery of the lamina. 14,18,40 Second, evidence from ex vivo 56,[67][68][69][70] and in vivo 44,[71][72][73][74] studies suggest that neural tissues at the periphery of the lamina often experience the largest IOPinduced strains. Modeling defects in this region can provide an upper-bound estimation of the influence of LC defects on IOP-induced mechanical insult to neural tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Recent years have seen important developments in the ability to directly measure ONH deformation, using various imaging modalities including histomorphometry,7 confocal microscopy,8 optical coherence tomography,9,10 microcomputed tomography,11 and second-harmonic generation imaging 12,13. High-resolution images can be generated by using these techniques, but tissue penetration depth and/or displacement resolution are often limited.…”
mentioning
confidence: 99%